HUBUNGAN PENGETAHUAN DAN SIKAP ORANG TUA DENGAN PERILAKU PENCEGAHAN K.E.P (KURANG ENERGI PROTEIN) BALITA DI WILAYAH KERJA PUKESMAS MOJOWARNO JOMBANG - Ratnaningsih, Tri (JURNAL KEPERAWATAN BINA SEHAT, 2009)
Protein Energy Malnutrition (PEM) know as K.E.P is national seriosly problem in this monetary crisis situation. To increase the children nutrient status with K.E.P not only by a medic approach and health service, but aslso involve the knowledge aspect, attitude and parent’s behavior. The purpose of this research s in order to increasing the children nutrient stastus by K.E.P.The design of this research is cross sectional research. The population of this research is parent who have the children with K.E.P problem at working area of Mojowarno Public Health Center in Jombang City. A total sample of this research is 48 respondents and the samples were taken by purposeive sampling method. Independent variabel is knowledge and parent’s behavior in K.E.P and dependent variabel is parent’s behavior in increasing of children nutrient status with K.E.P. The data collecting method of this research is questionnaire. The data analizing that used is Sperman Rank Coreclation test with the meaning level value ip ≤ 0.005.The result of this research available get the values and the statements i.e. it have relationship between parent’s knowledge level in K.E.P and parent’s behavior with low correlation that showed in the value p = 0.034, r = 0.307 and have the showed in the value p = 0.004, r = 0.411.The conclussion of this research is knowledge and parent’s behavior in K.E.P that have ralationship between parent’s behavior in increasing the children nutrient status with K.E.P and the middle or low correclation.Keyword : knowledge, attitude, behavior, nutrient status, children, K.E.P